AI-Supported Automated Subject Indexing and Metadata Management with Annif and Finto AI at the National Library of Finland - Schumann, Anna-Lea; Mergel, Ines (Springer, 2025)
The National Library of Finland developed and implemented an automated subject indexing and classification tool, Annif, which is now also used by other National Libraries. The tool is integrated into Finto AI, an in-house metadata management system launched in 2020. These two AI-driven solutions were created by the growing volume of digitally collected data, the extensive digitisation of paper archives, inadequate AI support for various Finnish languages, and a lack of transparency in the services offered by external providers on the market. The successful implementation of Annif and Finto AI can be attributed to the strong collaboration between the project team and their external stakeholders, such as other National Libraries or universities, as well as the awareness within the Finnish National Library. Use cases, for example, from the University of Jyväskylä, highlight the value of these AI-driven solutions. However, challenges remain, such as identifying hidden errors in the automatically generated records. Fortunately, the National Library’s extensive in-house expertise allows for the immediate detection of mistakes in both the code and the generated records.
Keywords: Artificial Intelligence; National Libraries; National Library of Finland; National Library; AI; Annif; Finto AI; Automated subject indexing; External stakeholders; fi=Julkisjohtaminen|en=Public Management|